Effect of Aerobic (Low Impact) on Blood Pressure in Hypertension Patients - Rohmah RAN; T I Puspita; Ikrima Rahmasari (Proceeding of International Conference on Science, Health, And Technology, 2019)
Hypertension is known as high blood pressure and is often referred to as a "silent killer" because it occurs without signs and symptoms, so that patients do not know if they are exposed to hypertension. Hypertension attacks more people in middle age, namely in the 55-64 years age group. One way to effectively treat hypertension is by exercise, one type of exercise that is beneficial and does not cause adverse effects is aerobic exercise (low impact). The method in this study is quantitative with a pre-experimental research design with one group pre-test design post-test design. The sample of this study was 18 elderly with hypertension. Aerobic gymnastic instruments use aerobics and music videos. Measurement of blood pressure before and after aerobic exercise (low impact) with a spygmomanometer. Data analysis using the Wilcoxon test. with results on systolic blood pressure obtained Z values ​​= -4.001 with p = 0,000 (p <0.05) and diastolic blood pressure values ​​Z = -3,834 with p = 0,000, (p <0.05). The conclusion of this study is the effect of aerobic exercise (low impact) on blood pressure in patients with hypertension.